PENGARUH LEVEL PEMBERIAN PUPUK ECO FARMING (EF) TERHADAP PERTUMBUHAN DAN PRODUKSI RUMPUT GAJAH (Pennisetum purpureum Cv. Pakchong): Effect of Eco-Farming (EF) Fertilizer Levels on Growth and Production of Elephant Grass (Pennisetum purpureum Cv. Pakchong) - Budiman Budiman; Nurjaya Nurjaya (Buletin Nutrisi dan Makanan Ternak, 2022)
This study aimed to determine the effect of the level of application of ecofarmingfertilizer on the growth, production, and production of forage elephantgrass Cv. Pakchong. The experiment was arranged in a completely randomizeddesign with four treatments and four replications. The treatments consisted of: P0= 0 ml EF + 100 ml water (control); P1 = 4 ml EF/polybag + 100 ml water; P2 = 6ml EF/polybag + 100 ml water; P3 = 8 ml EF/polybag + 100 ml water. The resultsshowed that using different eco-farming fertilizers had no effect (P>0.05) on plantheight, number of tillers, number of leaves per plant, leaf length and width, stemdry matter production, forage dry matter production, leaf stem ratio, but did havean effect (P<0.05) on leaf dry matter production. It was concluded that theapplication of eco-farming fertilizer level did not affect the growth parameters anddry matter production of stems but did affect the increase in leaf dry weight ofelephant grass Cv. Pakchong.